POTENSI TRICHODERMA ISOLAT LOKAL SEBAGAI DEKOMPOSER SERASAH AKASIA (Acacia mangium) - Junita, Yulita; Suryantini, Rosa; Wulandari, Reine Suci (Universitas Tanjungpura, 2017)
Acacia produce a litter of in the forest industry plants are not utilized and difficult to decompose so it can be acumulotion of litter. The decomposition can be accelarared with the use of local Trichoderma isolates. But, it is not yet known the best local isolates and concentration of trichoderma as the decomposers of acacia litter. The aim of research to get the kind of local isolate and concentrate the best Trichoderma as decomposers of litter acacia. This research was conducted at the Laboratory of Silviculture Forestry University Tanjungpura Pontianak for 8 months starting from the preparation, execution, analisis this research method is done in the form of factorial experimental design completely randomized experimental with design. The treatments consisted of two factors, namely the local isolates of Trichoderma (Trichoderma sp. 1 = T1; Trichoderma sp. 2 = T2; Trichoderma sp. 3 = T3, Trichoderma sp. 4 = 4) and the concentration of Trichoderma suspension (10-5 ml = k1, 10-6 ml = k2, 10-7 = k3). The combination total of treatments were 12 units with three replications. The observed data is decomposed pH value before and after decomposed, the mycelium dry weight, the percentage of Â moisture litter, the C / N ratio and the content of phosphor (P) and potassium (K). Based on the results turned out to isolate Trichoderma sp 2 with a concentration of 10-5 is the best decomposers to accelerate proser acacia mangium litter decomposition. Time or the length of the decomposition can be extended for more or less five months to get maximum results.Keywords: Acacia mangium, Concentration, Decomposers, Litterâ€™s, Trichoderma.